Emergent characteristics of rockfall inventories captured at a regional scale. Issue 12 (28th July 2020) - Benjamin, Jessica; Rosser, Nick J.; Brain, Matthew J.
Abstract: High‐resolution rockfall inventories captured at a regional scale are scarce. This is partly owing to difficulties in measuring the range of possible rockfall volumes with sufficient accuracy and completeness, and at a scale exceeding the influence of localized controls. This paucity of data restricts our ability to abstract patterns of erosion, identify long‐term changes in behaviour and assess how rockfalls respond to changes in rock mass structural and environmental conditions. We have addressed this by developing a workflow that is tailored to monitoring rockfalls and the resulting cliff retreat continuously (in space), in three‐dimensional (3D) and over large spatial scales (>10 4 m). We tested our approach by analysing rockfall activity along 20.5 km of coastal cliffs in North Yorkshire (UK), in what we understand to be the first multi‐temporal detection of rockfalls at a regional scale. We show that rockfall magnitude–frequency relationships, which often underpin predictive models of erosion, are highly sensitive to the spatial extent of monitoring. Variations in rockfall shape with volume also imply a systemic shift in the underlying mechanisms of detachment with scale, leading us to question the validity of applying a single probabilistic model to the full range of rockfalls observed here. Finally, our data emphasize the importance of cliff retreat as an episodic process. Going forwards, there will a pressing need to understand and model the erosional response of such coastlines to rising global sea levels as well as projected changes to winds, tides, wave climates, precipitation and storm events. The methodologies and data presented here are fundamental to achieving this, marking a step‐change in our ability to understand the competing effects of different processes in determining the magnitude and frequency of rockfall activity and ultimately meaning that we are better placed to investigate relationships between process and form/erosion at critical, regional scales. © 2020 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd Abstract : Airborne LiDAR is used to create a high‐resolution and multi‐temporal 3D rockfall inventory along > 20 km of coastal cliffs. Rockfall magnitude‐frequency relationships are highly sensitive to the spatial scale of monitoring. Results mark a step‐change in our ability to investigate relationships between process and erosion at regional scales.